1987
DOI: 10.1172/jci113148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intranasal histamine on nasal mucosal blood flow and the antidiuretic activity of desmopressin.

Abstract: The effects of exogenous histamine on nasal mucosal blood flow and the systemic activity of intranasally administered desmopressin, a vasopressin analogue, were studied in normal volunteers. Ten subjects received either saline or histamine (1, 20, 100, and 500 pg) by intranasal spray. Maximal nasal mucosal blood flow response, determined by laser doppler velocimetry, demonstrated a signifcant (P < 0.05) linear relationship to histamine dose. Eight additional subjects received each of the following intranasal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The majority have used some type of fixation to the head of the patient, as a head-band [3,[7][8][9][10] or a bicycle helmet [11], Druceet al [6] used audio headphones with a clamp attached for the probe. Olanoff et al [12] used eith er an earphone headset or a chin rest with an adjustable clamp for the probe. Rangi et al [13] used an adjustable metal bar and a nasal cannula.…”
Section: Discussionmentioning
confidence: 99%
“…The majority have used some type of fixation to the head of the patient, as a head-band [3,[7][8][9][10] or a bicycle helmet [11], Druceet al [6] used audio headphones with a clamp attached for the probe. Olanoff et al [12] used eith er an earphone headset or a chin rest with an adjustable clamp for the probe. Rangi et al [13] used an adjustable metal bar and a nasal cannula.…”
Section: Discussionmentioning
confidence: 99%
“…These are similar to the changes that occur in the common cold and hay fever, the relationship of which to nasal absorption is uncertain. Larsen et al (1987) reported that histamine-induced rhinitis did not influence nasal absorption of buserelin, whereas Olanoff et al (1987) reported that the nasal absorption of desmopressin was improved after a similar treatment.…”
Section: Safety Considerationsmentioning
confidence: 99%
“…Vasoconstrictors have frequently been used in combination with other drugs in nasal formulations to prevent adverse systemic effects by reducing systemic absorption (Urtti and Kyyrönen, 1989;Kyyrönen and Urtti, 1990a,b;Luo et al, 1991;Jä rvinen and Urtti, 1992) or to prolong the duration of action by reducing clearance from the delivery site (Adams et al, 1976;Liu et al, 1995). Vasodilators have also been used to enhance systemic bioavailability of drugs (Olanoff et al, 1987;Urtti and Kyyrönen, 1989). We hypothesized that reduced systemic absorption with a vasoconstrictor would increase residence time and increase deposition in the nasal epithelium.…”
mentioning
confidence: 99%